Reduced Cell Yields of Mouse Cell Line Cultures After Exposure to Homogenates of Multiple Sclerosis Tissues - Carp, Richard I. (1974)
The total cell yields in cultures of a mouse cell line termed “PAM” were reduced markedly after exposure to multiple sclerosis (MS) homogenates. The reductions were noted as early as the second subcultivation. The effect was produced by eight of eight MS brain homogenates and three of three MS spleen homogenates; the samples were from 10 MS cases. The reduction in total cell yields (compared to medium-treated cultures) was not observed after exposure to homogenates, six brain and two spleen, from eight non-MS cases. The effect was produced by the 50-nm filtrate of a pool of MS brain homogenates. Five of the MS-inoculated cultures were maintained for 18 subcultivations, and the reduction in total cell yields persisted throughout the series. The capacity to induce the reduction in cell yields was present in cell-free lysates from five of five MS cultures at passage 18, as was the capacity to cause a decrease in the polymorphonuclear neutrophils in the peripheral blood of mice. Calculation of the dilution effect (at least 10(18)-fold) that had occurred by the end of the passage series proved that the factor(s) causing the cell change in culture and the polymorphonuclear neutrophil change in mice had replicated in PAM cells.